Implementasi Program Penguatan Pendidikan Karakter Siswa Melalui Cerita Rakyat - Kasma F. Amin (PT FORMOSA CENDEKIA GLOBAL, 2022)
Character Education Strengthening Program (PPK) in schools can be done one of them through learning local folklore. This paper discusses the implementation of strengthening student character education through local folklore. The method used is observation, interviews and classroom action research with a sample of SMAN 13 Maros class XII. The results of the study were concluded through three stages, namely: 1) the results of observations of the Indonesian language learning textbook material used showed that the material for strengthening character education through local folklore had not been included. 2) After carrying out literary learning modeling with local folklore material, it shows an increase in students' understanding of several folklore titles, characters, various characters, story content, and setting. 3) there is an increase in students' understanding of the story text regarding the characters of the story characters such as brave characters, patient characters, loyal characters, and intelligent characters.